ASSESSING THE IMPACT OF ONLINE LEARNING COMMUNITIES ON COLLABORATIVE LEARNING AND KNOWLEDGE SHARING - Roni Subhan; Vann Sok; Sokha Dara (Journal International Inspire Education Technology, 2026)
The increasing integration of online learning communities into educational settings has sparked interest in their potential to enhance collaborative learning and knowledge sharing. While these communities are widely recognized for fostering peer interaction and engagement, their specific impact on learning outcomes remains underexplored. This study aims to assess the impact of online learning communities on collaborative learning and knowledge sharing among university students. A mixed-methods approach was employed, combining quantitative surveys to measure collaboration and knowledge sharing, alongside qualitative interviews to capture student experiences. The experimental group, which participated in online learning communities, showed significant improvements in both perceived collaboration and knowledge sharing compared to the control group, which engaged in traditional learning methods. The post-survey results indicated higher levels of interaction, peer support, and knowledge exchange within the experimental group. These findings suggest that online learning communities foster an environment conducive to collaborative learning, enhancing students' engagement and their ability to share knowledge. The study contributes to the growing body of research on online education by providing empirical evidence of the benefits of these communities. Future research should explore the long-term effects of online learning communities and examine how specific platform features can further enhance collaborative learning.